Molecular basis of various forms of maple syrup urine disease in Chilean patients. Issue 5 (6th May 2021) - Campanholi, Diana Ruffato Resende; Margutti, Ana Vitoria Barban; Silva, Wilson A.; Garcia, Daniel F.; Molfetta, Greice A.; Marques, Adriana A.; Schwartz, Ida Vanessa Döederlein; Cornejo, V.; Hamilton, Valerie; Castro, Gabriela; Sperb‐Ludwig, Fernanda; Borges, Ester S.; et al.
ABSTRACT: Background: Maple syrup urine disease (MSUD) is an autosomal recessive inherited metabolic disorder caused by the deficient activity of the branched‐chain α‐keto acid dehydrogenase (BCKD) enzymatic complex. BCKD is a mitochondrial complex encoded by four genes: BCKDHA, BCKDHB, DBT, and DLD . MSUD is predominantly caused by mutations in the BCKDHA, BCKDHB, and DBT genes which encode the E1α, E1β, and E2 subunits of the BCKD complex, respectively. The aim of this study was to characterize the genetic basis of MSUD in a cohort of Chilean MSUD patients by identifying point mutations in the BCKDHA, BCKDHB, and DBT genes and to describe their impact on the phenotypic heterogeneity of these patients. Methods: This manuscript describes a cross‐sectional study of 18 MSUD patients carried out using PCR and DNA sequencing. Results: Four novel pathogenic mutations were identified: one in BCKDHA (p.Thr338Ile), two in BCKDHB (p.Gly336Ser e p.Pro240Thr), and one in DBT (p.Gly406Asp). Four additional pathogenic mutations found in this study have been described previously. There were no correlations between the genotype and phenotype of the patients. Conclusion: If MSUD is diagnosed earlier, with a newborn screening approach, it might be possible to establish genotype‐phenotype relationships more efficiently. Abstract : This manuscript describes a cross‐sectional study of 18 MSUD patients carried out using PCR and DNA sequencing. Four novel pathogenic mutations were identified: one in BCKDHA (p.Thr338Ile), two in BCKDHB (p.Gly336Ser e p.Pro240Thr), and one in DBT (p.Gly406Asp). Four additional pathogenic mutations found in this study have been described previously. There were no correlations between the genotype and phenotype of the patients.